Liver/kidney microsomal antibody type 1 targets CYP2D6 on hepatocyte plasma membrane. Issue 4 (1st April 2000) - Muratori, L; Parola, M; Ripalti, A; Robino, G; Muratori, P; Bellomo, G; Carini, R; Lenzi, M; Landini, M P; Albano, E; Bianchi, F B
Abstract : BACKGROUND: Liver/kidney microsomal antibody type 1 (LKM1) is the marker of type 2 autoimmune hepatitis (AIH) and is detected in up to 6% of patients with hepatitis C virus (HCV) infection. It recognises linear and conformational epitopes of cytochrome P450IID6 (CYP2D6) and may have liver damaging activity, provided that CYP2D6 is accessible to effector mechanisms of autoimmune attack. METHODS: The presence of LKM1 in the plasma membrane was investigated by indirect immunofluorescence and confocal laser microscopy of isolated rat hepatocytes probed with 10 LKM1 positive sera (five from patients with AIH and five from patients with chronic HCV infection) and a rabbit polyclonal anti-CYP2D6 serum. RESULTS: Serum from both types of patient stained the plasma membrane of non-permeabilised cells, where the fluorescent signal could be visualised as discrete clumps. Conversely, permeabilised hepatocytes showed diffuse submembranous/cytoplasmic staining. Adsorption with recombinant CYP2D6 substantially reduced plasma membrane staining and LKM1 immunoblot reactivity. Plasma membrane staining of LKM1 colocalised with that of anti-CYP2D6. Immunoprecipitation experiments showed that a single 50 kDa protein recognised by anti-CYP2D6 can be isolated from the plasma membrane of intact hepatocytes. CONCLUSIONS: AIH and HCV related LKM1 recognise CYP2D6 exposed on the plasma membrane of isolated hepatocytes. This observation supports the notion that anti-CYP2D6 autoreactivity may be involved in the pathogenesis of liver damage.